Respostas do predador Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) aos compostos orgânicos voláteis de folhas de Eucalyptus urograndis (Myrtaceae) e identificação dos componentes de seu óleo essencial - Borges, David Jackson Vieira (2020)
Plants are capable of producing volatile compounds, chemical signals that offer defense against stress agents and allow communication with the environment. It is known that herbivory induces plants to produce volatile compounds that attract natural enemies, however there are few studies that evaluate the direct effects of the relationship between plants and predators without considering the participation of herbivores. This evaluation can provide important information for the study of ecological interactions that support the development of biological pest control strategies. In this context, the present work had as objectives: (i) to verify the behavioral responses of Chrysoperla externa (Hagen, 1861) larvae (Neuroptera: Chrysopidae) to the volatiles of young and mature leaves, intact and with eucalyptus injury Eucalyptus urograndis (Myrtaceae ); (ii) investigate the compounds of the essential oils of this species of eucalyptus and their effects on insects. With the use of the “Y” olfactometer system, it was possible to verify the responses of the chrysopids to the combinations of odors emitted by the eucalyptus leaves. The results of the olfactometry tests showed that the predatory insects respond to the volatiles emitted by the plants without the participation of herbivores in the experiments. In addition, the preference of chrysopids larvae for odors emitted by new leaves with simulated injury was observed. The essential oil of the eucalyptus leaves was obtained by hydrodistillation with subsequent identification of the compounds through the gas chromatograph coupled to a mass spectrometer - CG-MS. Compounds were identified that other studies with the same species had not identified. Among the identified compounds, Eucaliptol, α-Terpineol and Aromadendrene have a known action against groups of insects, while α-Terpinyl acetate has an attractive action to certain groups of insects. The work contributed with basic data on the potential use of eucalyptus forests as maintainers of natural chrysopids populations, and suggests new studies to evaluate the essential oil components that can act as attractive to these insects.